Zjawiska glacitektoniczne w kopalni Bełchatów (2003-2005) = Glaciotectonic fenomena in Bełchatow mine (open pit) (2003-2005) - Bruj, Małgorzata; Krysiak, Zofia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Glaciotectonic structures in Pleistocene deposits of Bełchatow Mine have been studied since 2003 to 2005y. Four Western (highest) walls of cover were mapped and the part of the Northern wall too (fig. l). Numerous glaciotectonic structures, sediment flows or liquefaction and neotectonic features were noticed.
Keywords: X jubileuszowe sympozjum glacitektoniki